An investigation into the effect of scanning pattern and heat treatment on the mechanical properties of Inconel 718 in the direct metal deposition process - Fareed Kermani; Reza Shoja-Razavi; Karim Zangenemadar; Mohammadreza Borhani; Mohammad Gavahian (Journal of Materials Research and Technology, 2023)
In this study, the additive manufacturing process of Inconel 718 superalloy on a homogenous forged substrate with three different patterns is investigated, followed by studying the samples’ mechanical properties and heat treatment effect on them. After additive manufacturing, the tensile properties of the samples were investigated by form of 50%-forging specimens and 50%-additively manufactured specimens. Results showed the best tensile properties are obtained in a sample made with a circular pattern. Also, the difference in the tensile properties of the sample made parallel to the tensile axis, and the sample created in the vertical direction indicate the anisotropic behavior of the additively manufactured samples. After additive manufacturing of samples with parallel, perpendicular, and circular patterns, the ultimate strength increased by 7, 6, and 11% compared to the control sample (forging). Despite the strength increase, the ductility of the specimens decreased by 28, 20, and 11% compared to forging specimen. In the 100%-additively manufactured sample, the ultimate strength increased by 6%, and the ductility decreased by 45%. After investigating the pattern for mechanical properties, annealing heat treatment at 1080 °C for 1 h and two aging processes at 620 and 720 °C for 4 and 8 h, respectively, were performed to improve the properties and create a strengthening phase. The ductility of the sample made with a 50% circular pattern and 50% forging sample increased by 51% and 36% by annealing compared to the raw state and the control sample, respectively. Moreover, the hardness level and ductility became uniform and increased after annealing.